The Effect of Reputation on Online Repurchase Intention of Fruits/Vegetables in Indonesia With Emotional and Perceived Risk as Antecedent: Based on The Stimulus-Organism-Response Model - Amir Fikri; Rita Nurmalina; Mukhamad Najib; Megawati Simanjuntak (School of Business, Bogor Agricultural University (SB-IPB), 2019)
As the trend of online business shopping began to develop it is necessary to have a number of factors anticipated, among others, fresh vegetables/fruit online repurchase intention. The aim of this study is to explain the determinant which influences repurchase intention of customer who buys fruits and vegetables by using e-commerce in Indonesia. Stimulus-Organism-Response Model are used as the basic concepts in this study. The sample collection methods in this study is convenience sampling from 331 respondents who met the criteria. Collected data is analysed using Structural Equation Model (SEM) Lisrel 8.8 and SPSS 24.0 program for all variables. The result of the findings show that there is a significant influence between emotion and risk perceived towards online repurchase intention, and perceived risk give a negative impact to online repurchase intention and emotion. The reputation of e-retailers has no significant effect on perceived risk. Perceived risk has a significant influence on emotion and online repurchase intentions.This study found that emotion significantly influences willingness to online repurchase intention toward fresh vegetables/fruits in Indonesian’s e-shopper. This study will be useful to vegetables and fruits e-retailers as well as future researchers.Keywords: online repurchase intention, e-commerce, stimulus-organism-response model, reputation, emotion, perceived risk